الوعى المعلوماتى لدى المحامین بمحافظة المنوفیة :دراسة میدانیة - د. نها محمد عثمان (المجلة الدولية لعلوم المكتبات والمعلومات)
Explore the current study, the reality and the level of awareness of Cyberamong lawyers in Menoufia province, so the researcher asking anddiscussing the concept of awareness of Cyber to determine the identityand manifestations, and measure the extent of its availability in the studypopulation to identify the main difficulties faced by the population of thestudy, to support and raise awareness of Cyber among this society, andmake proposals to deploy and support a culture of awareness andinformational development of skills among the study population.